Alokasi Resource bagi Multicarrier-Low Density Sequence-Multiple Access - Linda Meylani; Nur Andini; Desti Madya Saputri; Iswahyudi Hidayat (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2022)
Multicarrier low-density sequence multiple access (MC-LDSMA) is a code domain type of non-orthogonal multiple access (NOMA) in a multicarrier system. Each user in this multiple access scheme has a non-orthogonal code to one another. Each user is only allowed to access dv from the available N resources and there are only dc users from the total of J users accessing the same resource. The non-orthogonal nature causes the MC-LDSMA system to have a higher overloading factor than other orthogonal multicarrier systems. This condition causes MC-LDSMA to become one of the multiple access techniques used in underlay cognitive radio communication systems, where secondary users (SUs) are permitted to access resources owned by primary users (PUs). This paper proposed a resource allocation algorithm for MC-LDSMA in an underlay cognitive radio system. The proposed algorithm aims to increase the number of SUs accessing PUs resources while maintaining the SUs quality factor. The system built consisted of I PUs and J SUs. PUs in the system was assumed to be orthogonal so that they did not interfere with each other. At the same time, some J SUs simultaneously accessed resources owned by PU using the MC-LDSMA multiple access schemes. The proposed algorithm considered several factors, including the parameters dc, dv, SU target signal-to-noise ratio (SNR), and the interference tolerance limit desired by PU. Performance parameters were indicated by the outage probability (OP), the throughput of PU and SU, and the ratio of the number of SUs that were allocated less than dv resources. The simulation results suggest that all performance parameters are affected by the number of resources accessed by each user, dv, the target SNR of SU, and the interference limit determined by PU.